2012
DOI: 10.1093/czoolo/58.3.463
|View full text |Cite
|
Sign up to set email alerts
|

Can sexual selection and disassortative mating contribute to the maintenance of a shell color polymorphism in an intertidal marine snail?

Abstract: Littorina fabalis is an intertidal snail commonly living on the brown algae Fucus vesiculosus and showing frequent shell-color polymorphisms in the wild. The evolutionary mechanism underlying this polymorphism is currently unknown. Shell color variation was studied in mated and non-mated specimens of this species from different microareas in one locality from NW Spain, in order to estimate sexual selection and assortative mating that may (still) be operating in this population. The analyses across microareas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Two samples (1990 and 2011) were reanalyzed from previous studies (Rolán‐Alvarez and Ekendahl and Rolán‐Alvarez et al. ), while the remaining two samples are described here for the first time (2012 and 2013; see raw data displayed in Table S1). Overall, data on a total of 918 mated and 1506 unmated specimens was collected.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two samples (1990 and 2011) were reanalyzed from previous studies (Rolán‐Alvarez and Ekendahl and Rolán‐Alvarez et al. ), while the remaining two samples are described here for the first time (2012 and 2013; see raw data displayed in Table S1). Overall, data on a total of 918 mated and 1506 unmated specimens was collected.…”
Section: Methodsmentioning
confidence: 99%
“…Further details on methods have been given elsewhere (Rolán‐Alvarez and Ekendahl ; Rolán‐Alvarez et al. ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotypic polymorphism in Littorinids is not just limited to L. saxatilis; Daniel Estévez (University of Vigo, Spain) gave a talk on L. fabalis, a snail species that occurs on brown algae along European shores and shows a clear polymorphism for shell colour with striking brown and yellow individuals (Rolán‐Alvarez et al., ). How this polymorphism is maintained is unclear; a previous study suggested it might be maintained by negative assortative mating, with males choosing females of different colours (Rolán‐Alvarez et al., ). Longitudinal data offer an opportunity to test the predictability of evolution, which is dependent on many factors, including the nature of selection, environmental variation and genomic interaction (Nosil et al., ).…”
Section: Sexual Selection and Mate Choicementioning
confidence: 99%
“…Rolán- Alvarez et al (2012) find that shell color in the marine intertidal snail Littorina fabalis is under sexual selection, but serves as the basis of consistent disassortative, not assortative, mating. In this instance, therefore, the sexually selected trait would tend to cause population cohesion, rather than divergence.…”
Section: Contributions To This Issuementioning
confidence: 99%